An Essential Role of Caspase 1 in the Induction of Murine Lupus and Its Associated Vascular Damage. Issue 1 (January 2014) - Kahlenberg, J. Michelle; Yalavarthi, Srilakshmi; Zhao, Wenpu; Hodgin, Jeffrey B.; Reed, Tamra J.; Tsuji, Noriko M.; Kaplan, Mariana J.
<x xml:space="preserve">Abstract</x> Objective Systemic lupus erythematosus (SLE) is a systemic autoimmune syndrome associated with organ damage and an elevated risk of cardiovascular disease resulting from activation of both innate and adaptive immune pathways. Recently, increased activation of the inflammasome machinery in SLE has been described. Using the mouse model of pristane‐induced lupus, we undertook this study to explore whether caspase 1, the central enzyme of the inflammasome, plays a role in the development of SLE and its associated vascular dysfunction. Methods Eight‐week‐old wild‐type (WT) or caspase 1−/− mice were injected intraperitoneally with phosphate buffered saline or pristane. Six months after injection, mice were euthanized, and the development of a lupus phenotype and vascular dysfunction was assessed. Results While WT mice exposed to pristane developed autoantibodies and a strong type I interferon response, mice lacking caspase 1 were significantly protected against these features as well as against pristane‐induced vascular dysfunction. Further, the development of immune complex glomerulonephritis, which was prominent after pristane exposure in WT mice, was significantly abrogated in caspase 1−/− mice. Conclusion These results indicate that caspase 1 is an essential component in the development of lupus and its associated vascular dysfunction and that it may play an important role in the cross‐talk between environmental exposures and autoimmunity development, thus identifying a novel pathway for therapeutic targeting.